How do you solve (3x - 7) - 5( x - 4) = 21?

2 Answers
Mar 18, 2018

x=-4

Explanation:

[0] (3x-7)-5(x-4)=21
First let's simplify by a product rule the term 5(x-4)
[1] (3x-7)-5*x-(5*-4)=21
We also have -a*-b=a*b, so:
[2] (3x-7)-5x+20=21
Parenthesis on (3x+7) are useless, so we have :
[3] 3x-7-5x+20=21
Let's put all numbers on the right part:
[4]3x-7+7-5x+20-20=21+7-20
[5]-2x=8
Finally let's Just divide by-2
[6]x=-4

Mar 18, 2018

x=-4

Explanation:

We can start by distributing the -5 to the (x-4) term. We get:

3x-7-5x+20=21

We can combine like terms to get:

-2x+13=21

We can subtract 13 from both sides to get:

-2x=8

Lastly, we can divide both sides by -2 to get:

x=-4

Hope this helps!